Duration Of Hemodialysis With Incidence Of Pruritus In The Hospital Santa Elisabeth Medan In 2024 - Sembiring, Friska; Ginting, Amnita; Sinurat, Samfriati; Togatorop, Afrina Irene Zepanya (Mata Pena Madani, 2025)
Hemodialysis therapy that patients with chronic kidney failure must undergo during their lifetime. The length of hemodialysis therapy that patients undergo has a different time – different for each individual, the hemodialysis process causes complications such as pruritus. Pruritus occurs in patients undergoing hemodialysis because during the dialysis process there is an increase in temperature and dilation of blood vessels, causing sweating and itching. This study aims to determine the long-term relationship between hemodialysis and the incidence of pruritus in chronic kidney failure patients undergoing hemodialysis. This study uses the Cross Sectional research method. The sampling technique uses total sampling, namely the number of patients undergoing hemodialysis as many as 65 respondents. Data collection was carried out using a questionnaire and the statistical test used was the Spearman rank test. p-value = 0.001 (p0.05) and a correlation coefficient of 0.493 which means that there is a relationship between Long Duration of Hemodialysis and the Incidence of Pruritus in Chronic Kidney Failure Patients Undergoing Hemodialysis.